2022
DOI: 10.21203/rs.3.rs-2057836/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hexavalent chromium tolerant fungal species identified from urban vegetable farm and effluent waste in Addis Ababa & Rift valley, Ethiopia

Abstract: Hexavalent chromium is resistant to degradation and sever toxic substance to environment and community health.Physico chemical treatment methods are demanding high cost, used large quantities of chemicals & energy, release large amount of secondary toxic degradants. Mycoremediation is an eco-friendly alternative treatment method. The main objective of this research is to isolate and characterize chrome (VI) tolerant yeast from farm soil & industry e uent for mycoremedation role. The screening and isolation of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has been suggested that the fungus Rhodotorula sp., Candida sp., Trichosporon sp., and Cryptococcus sp. acts as indicators of water contamination [14] . Additionally , yeasts are highly biodegradable to a variety of resistive and organic poisons [13] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the fungus Rhodotorula sp., Candida sp., Trichosporon sp., and Cryptococcus sp. acts as indicators of water contamination [14] . Additionally , yeasts are highly biodegradable to a variety of resistive and organic poisons [13] .…”
Section: Introductionmentioning
confidence: 99%